Analysis of Consumer Preferences for Instant Mangosteen (Garcinia mangostana L.) Powder Drink in Bogor Regency and City - Fadhilah Nur'azizah; Dase Hunaefi; Tjahja Muhandri (agriTECH, 2023)
The peel of mangosteen (Garcinia mangostana L.) constitutes a larger proportion of the fruit in comparison to its flesh. The peel extract product manufactured by nutraceutical industries does not require using the fruit flesh. To increase the shelf life and value of the product, the development of a mangosteen powder drink can be carried out. Therefore, this research aims to determine the characterization of initial raw materials and factors influencing consumer preferences for instant mangosteen powder drink to improve the acceptance of the product. The data collected were analyzed through descriptive statistics and the chi-square test. Furthermore, the chi-square test showed that demographic regions affected mangosteen fruit price, the level of preferences for the powder drink, consumption time, as well as feelings and interests of potential customers. The results of the Total Plate Count (TPC), Total Yeast and Mold Count (TYMC), and coliform microbiological test conducted on mangosteen purée raw materials met the quality requirements established by National Standardization Body (NSB) for fruit purées.